Mapping the Potential and the Development of Kendran as a Tourism Village Model in Bali - Ni Putu Nina Eka Lestari; I Nyoman Rasmen Adi; Ni Nyoman Reni Suasih; Alit Sumantri (Bali Membangun Bali: Jurnal Bappeda Litbang, 2020)
Purpose: (1) Compile a baseline study of the potential of tourist objects and attractions as well as the readiness of community participation in the Community Based Tourism development model and forms of collaboration with relevant stakeholders; (2) Strengthening institutional and community empowerment in developing Kendran Tourism Village, as a community-based tourism village; and (3) Establishment of cooperation models and policies that can be developed by local governments and related stakeholders. Research methods: the method of documentation, questionnaires, interviews, and FGD. The collected data was then analyzed using existing condition analysis techniques, ADO-ODTWA assessment, participatory rural analysis (PRA), SWOT analysis, MACTOR analysis, and MULTIPOL analysis. Findings: Kendran Village as a tourist village, as well as its readiness for development were quite potential. The main policies that need to be prioritized include increasing the capacity of rural communities, strengthening village tourism institutions, packaging attractions / attractions for creating branding, and expanding and maintaining markets. Implications: the development of a single destination tourist village is the creation of branding, while the policy to increase the capacity of rural communities has the highest value in the multiple destination tourist village scenario. Tourism development policy in the Province of Bali refers to the concept of sustainable and quality tourism, through various multi-sector policies.